2003
DOI: 10.1046/j.1440-1746.2003.03091.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of major histocompatibility complex and CTLA‐4 alleles in Brazilian patients with primary biliary cirrhosis

Abstract: Susceptibility to PBC in Brazil is not associated with HLA-DR and DQ antigens and CTLA-4 genotypes. TNFA alleles were not shown to influence disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…54 However, a study from Newcastle, UK did not confirm this alleged association. 15 Similarly, in the data obtained from Scottish, Brazilian, and Chinese series of patients with PBC, 43,55,56 and from a small population of patients undergoing liver transplantation for end-stage PBC, 57 no association of TNF genotypes with disease susceptibility or onset was observed.…”
Section: Mhc and Pbcmentioning
confidence: 92%
See 2 more Smart Citations
“…54 However, a study from Newcastle, UK did not confirm this alleged association. 15 Similarly, in the data obtained from Scottish, Brazilian, and Chinese series of patients with PBC, 43,55,56 and from a small population of patients undergoing liver transplantation for end-stage PBC, 57 no association of TNF genotypes with disease susceptibility or onset was observed.…”
Section: Mhc and Pbcmentioning
confidence: 92%
“…36 It is possible that positive association might be 41 This association was not confirmed in several other studies from different non-British European populations. 32,35,36,42,43 Moreover, other European studies suggested significant associations of PBC with DR3 29,35 and DPB1*0301, 44 while the most recent study from the United States demonstrated an association between DRB1*08-DQA1*0401-DQB1*04 haplotype and PBC, albeit in a minority of patients. 40 Finally, studies from Japan failed to provide a consistent picture of HLA class II associations with PBC.…”
Section: Mhc and Pbcmentioning
confidence: 97%
See 1 more Smart Citation
“…Although early studies found an association between SNP 49G coding and PBC [22][23][24], ensuing reports showed negative relationships with susceptibility [25][26][27][28][29][30] or a positive association with liver damage [31]. A recent investigation reported that rs231725 in the 3'…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of CTLA4 in PBC identified an association with the G allele of 49AG in both UK (69) and Chinese (58) populations, that was not confirmed in a small study from Brazil (31). However, a later study by the UK group which investigated additional SNPs across CTLA4 in an expanded patient population using a more suitable control group, failed to replicate their initial findings of the 49AG association with PBC, calling into question this SNPs relevance to disease (70).…”
Section: "Autoimmune" Genesmentioning
confidence: 98%